2017
DOI: 10.3390/rel8120257
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Dignity of Thai Adolescents Living with HIV

Abstract: (1) Background: Adolescents are a key asset and resource for the social and economic development of any country, with the potential to make a significant contribution to their families, communities and countries. Healthy and educated adolescents are important. However, there are still significant rates of death, illness and disease among adolescents in some countries, where HIV is one of the most prevalent causes of death in this group. Adolescents living with HIV may experience and encounter social restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Most of the participants described that the sources of spiritual support resulted from believing in God .3,7-8,26,28-31 On the other hand, PLWHA in Thailand indicated that the source of spirituality came from religious practice, family support and adherence to the Lord Buddha's teachings. [9][10][11]27 The above factors provided the PLWHA with the power to manage stressful life events and illness. The participants described the positive roles of spirituality in life.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the participants described that the sources of spiritual support resulted from believing in God .3,7-8,26,28-31 On the other hand, PLWHA in Thailand indicated that the source of spirituality came from religious practice, family support and adherence to the Lord Buddha's teachings. [9][10][11]27 The above factors provided the PLWHA with the power to manage stressful life events and illness. The participants described the positive roles of spirituality in life.…”
Section: Discussionmentioning
confidence: 99%
“…9 The above factors can cultivate inner strength for PLWHA who are Buddhists. [9][10][11] Illness Understanding and Self-acceptance: The participants perceived that a higher power or God had a purpose to inflicting this illness on them. He aimed at teaching the participants, changing lifestyles, creating relationships and forming connections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations